Pengelompokan Produksi Padi dan Beras Provinsi Jawa Timur dengan Metode Agglomerative Hierarchical Clustering - Hasim Azari; Dwi Hartanti; Aprilisa Arum Sari (Fakultas Teknik Universitas Hamzanwadi, 2024)
Paddy is a food crop that produces rice which is widely consumed for basic needs and has become a source of income for the Indonesian people. Often the need for rice continues to increase and cannot only rely on domestic production, so it is necessary to optimize paddy producing areas. Grouping rice-producing areas needs to be done to identify production potentials and areas that require improvement. This research aims to group paddy and rice production based on districts/cities in East Java Province. The method used is Agglomerative Hierarchical Clustering (AHC) with the best algorithm, namely average linkage based on the highest cophenetic correlation of 0.8478. The research results showed 4 clusters: cluster 1 (high) with 4 districts, cluster 2 (low) with 18 districts, cluster 3 (medium) with 7 districts, and cluster 4 (very low) with 9 cities. The silhouette coefficient test is 0.6347, close to 1, thus indicating good clustering. These results can be used as a reference for the government and society in optimizing paddy and rice production to maintain the country's food security